Design And Development Of A Pond Water Quality Monitoring Device Using The GSM SIM-800L Module - Burhanudin, M. Dean (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2024)
The current pond water monitoring systems are still lacking, necessitating innovations in efficient and effective monitoring technology. This study aims to design and develop a pond water monitoring system using SIM800L and ESP32 modules. The method used in this research is development research, which includes the stages of design, creation, and testing of the device. This monitoring system is equipped with TDS sensors, temperature sensors, and pH sensors to measure pond water quality in real-time. The test results show that the developed device can accurately monitor pond water quality and transmit data to a server via the GSM network. In conclusion, this device is effective and can be used by users to practically and efficiently monitor pond water, thereby helping to maintain pond water quality and support better aquaculture